The teeny tiny woman - O'Connor, Jane; Alley, R. W. (New York : Random House, 1986)
A teeny tiny woman, who puts a teeny tiny bone she finds in a churchyard away in a cupboard before she goes to sleep, is awakened by a voice demanding the return of the bone.
Keywords: Children's stories